PENGEMBANGAN MEDIA POP UP BOOK UNTUK MENINGKATKAN MINAT BACA DALAM PEMBELAJARAN BAHASA INDONESIA MATERI DONGENG PADA KELAS III SDN JIA - Fira Rofita; Nunung Fatimah; Fakhri Khusaini (STKIP Subang, 2025)
This study aims to develop a Pop-Up Book as a learning medium to increase students' reading interest in Indonesian language lessons, specifically in folktale material for third-grade students at SDN JIA. The background of this research is the low reading interest among students, which is caused by the lack of engaging instructional media. This research adopts the Research and Development (R&D) method using the ADDIE development model, which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. The Pop-Up Book media was developed and validated by material and media experts, with validation results showing it to be highly feasible—100% from media experts and 86.6% from material experts. The trials were conducted in two phases: small-group and large- group trials. Teacher responses to the media reached 100%, while student responses were categorized as very practical, with results of 80.5% in the small group and 92.8% in the large group. The effectiveness of the media was tested through pretest and posttest assessments, showing an increase in scores from 35.7% to 92.1%. The N-Gain score was 0.87, which falls into the high category. These results indicate that the Pop-Up Book media is effective in improving the reading interest of third-grade students at SDN JIA. Therefore, the Pop-Up Book can be considered an innovative alternative in teaching folktales in primary school Indonesian language lessons.